SPE Annual Technical Conference and Exhibition 1996
DOI: 10.2118/36426-ms
|View full text |Cite
|
Sign up to set email alerts
|

Scleroglucan Biopolymer Enhances WBM Performances

Abstract: Thm paper was selected for presentation by an SPE Program Commmee following rewew of mformal!cm ccmamed m an abstract subnwled by the author(s) Con!ents of the paper, as presented, have nol been reviewed by the SO.aety of Petroleum Engineers and are $u@ect to correctmn by the author(s I The mafenal, as rrasented, does not necessarily reflect any pas!bon of the ?,ocaetyof Petroleum Engineers, Its offcers, or members Papars presented at SPE meetmgs am Sub)ect to pubhcat,on rev,ew by Edttorlal Committees of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In the field of enhanced oil recovery (EOR) scleroglucan is assessed as environmentally friendly viscosifying agent in virtue of its no toxicity and biodegradability. Indeed, it is quite suitable for formulating water based drilling muds to be employed in harsh environments owing to its good stability towards high salinities, temperatures and alkaline conditions, moderate interactions with surfactants and its robust shear tolerance (Baba Hamed & Belhadri, 2009;Gallino, Guarneri, Poli, & Xiao, 1996;Kulawardana et al, 2012;Sveistrup, van Mastrigt, Norrman, Picchioni, & Paso, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of enhanced oil recovery (EOR) scleroglucan is assessed as environmentally friendly viscosifying agent in virtue of its no toxicity and biodegradability. Indeed, it is quite suitable for formulating water based drilling muds to be employed in harsh environments owing to its good stability towards high salinities, temperatures and alkaline conditions, moderate interactions with surfactants and its robust shear tolerance (Baba Hamed & Belhadri, 2009;Gallino, Guarneri, Poli, & Xiao, 1996;Kulawardana et al, 2012;Sveistrup, van Mastrigt, Norrman, Picchioni, & Paso, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Xanthan gum (XCD) is currently the most popular biopolymer used as structuring agent to dispersed water-base drilling muds. As the bibliographical data shows (Cannell et al, 1988;Kalpakci et al, 1990;Riverq and Nolk, 1992;Gallino et al, 1996;Navarrete and Coffey, 2000;Lange and Keilhofer, 2004;Howard et al, 2015, Fortenberry et al, 2017 the alternative structuring agent that might be employed in drilling muds composition is scleroglucan bio synthesized with the participation of fungi of the genus Sklerotinum. Its chemical structure determines high thermal resistance and multivalent metal cations resistance and salinity.…”
Section: Biopolymers Usage In Drilling Mudsmentioning
confidence: 99%
“…There are two features of the scleroglucan structure determining its special properties, the nonionic character and the twisted polymer chains into the triple helical structure. All authors of the publication (Kalpakci et al, 1990;Rivenq and Nolk, 1992;Fjelde and Stavland, 1995;Gallino et al, 1996;Navarreta et al, 2000) agree on the unique thermal resistance of scleroglucan but the results they present often differ. Their studies confirmed the thermal stability of scleroglucan at 90°C for 500 days and at 100°C for 60 days.…”
Section: Biopolymers Usage In Drilling Mudsmentioning
confidence: 99%
“…Scleroglucan has been proposed as a better alternative to xanthan gum for drilling fluid compositions [228]. It is produced by aerobic fermentation of d-glucose by such microorganisms.…”
Section: Scleroglucanmentioning
confidence: 99%